PERAN GURU DALAM MENCEGAH PERILAKU BULLYING PADA PESERTA DIDIK DI SD NEGERI 9 GADUNG KECAMATAN GADUNG KABUPATEN BUOL - Sri Ayu S. Malik; Najamuddin Petta Solong; Sitti Rahmwati Talango (Al-mujahidah, 2026)
This study aims to determine the form of bullying behavior and the role of teachers in preventing bullying behavior in students at SD Negeri 9 Gadung, Gadung District, and to determine the obstacles and efforts of teachers in preventing bullying behavior in students at SD Negeri 9 Gadung, Gadung District, Buol Regency. This study uses a descriptive qualitative method with a phenomenological approach. Data collection through: observation; interviews and documentation. Data analysis techniques use data reduction, data presentation and conclusion drawing. The results of this study are 1) The form of bullying behavior in students that occurred at SD Negeri 9 Gadung is divided into two, the first is physical bullying such as pushing, pulling the hijab, damaging friends' belongings and extortion. Second is verbal bullying such as giving insults, making fun of parents, and demeaning in the form of gossip. 2) The role of teachers in preventing bullying behavior in students at SD Negeri 9 Gadung is carried out through the role of a guide, the role as a facilitator, the role as a role model, the role of a motivator, the role as a mediator. 3) The first obstacle is students who do not report, second is the limited time teachers have to supervise at school, third is the students' social circle which has a bad influence, and fourth is the students' parents who rarely respond to calls from the school..